Base fabric for materials and its manufacturing method

By using a fabric base cloth composed of 6.6CN/DTEX ~ 8.5cn/DTEX strength fiber, it solves the problem of expansion, gas tightness and storage of large airbags in high temperature environments, and realizes low dynamic breathability and high fever and stability Sexual effect.

CN115349037BActive Publication Date: 2025-01-24ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180024467.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-26
Publication Date
2025-01-24
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

The prior art is difficult to provide stable deployment, airtightness and storage for large airbags under high temperature environments, and the pyrotechnical inflators have problems with high temperature gas.

Method used

Uses a fabric base fabric for materials composed of fibers with a strength of 6.6cN/dtex ~ 8.5cN/dtex. It is not resin coated, laminated or impregnated. The E1 of the warp and weft yarns are both 3MPa ~ 25MPa, and the E2 is 10MPa. ~30MPa, measured by ASTM D6479, with low dynamic air permeability and high thermal stability.

Benefits of technology

In high temperature environments, it can effectively inhibit the mesh of the border between the expansion and non -expansion parts, maintain low dynamic breathability, ensure that the airbags are not easy to break, and are suitable for high -temperature applications of large -scale airbags.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115349037B_ABST
    Figure CN115349037B_ABST
Patent Text Reader

Abstract

Provided is a base fabric for materials, which has a suppressed mesh at the boundary between the expansion part and the non-expansion part when a bag is made, has low dynamic air permeability, and exhibits the characteristics of being difficult to break even at high temperatures, and a method for making the same. The base fabric for materials described in the present invention is characterized in that it is composed of fibers with a specified yarn strength, and the surface of the fabric is not subjected to resin coating, lamination or resin impregnation treatment, and the E1 of the warp and weft yarns of the base fabric for materials are both 3MPa to 25MPa, and the E2 is both 10MPa to 30MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a base fabric for materials and a method for making the same. Background Art

[0002] In recent years, airbags have become indispensable as a safety device for protecting vehicle occupants. As the characteristics required of airbags, they are required to have strength that can withstand impacts during driving and scratches on surrounding components; airtightness for stable deployment within the necessary time; flexibility that can be stored in a limited storage space; and compactness. In particular, as a recent trend, research has been conducted to strengthen the protection of the front pillar from the influence of tilted impacts and to cope with the posture of any occupant during automatic driving, requiring a wider range of protection, thereby increasing the capacity of the airbag. On the other hand, the airbag storage section is further limited due to the design of the interior of the vehicle. Therefore, the amount of deployment gas increases due to the increase in the volume of the airbag, and the requirements for the characteristics of being able to withstand the large stress at the boundary between the inflation section and the non-inflation section and exert airtightness are increased. Furthermore, it is increasingly necessary to achieve the opposite characteristics of increased volume and improved storage of the airbag. In addition, in order to reduce unit costs, pyrotechnic inflators also have a tendency to increase the temperature of the gas due to the simplification of the structure, and the above characteristics need to be met when deployed in a higher temperature environment.

[0003] In order to solve these problems, the following patent document 1 discloses the following technology: by having a specific amount of a specific substance on the fiber surface, the friction between the single yarns is reduced, the stress applied to the yarn during weaving is used to promote the flattening of the yarn, the airtightness when the base cloth is made is increased, and the storage property is improved by imparting softness. However, the document does not record the effect at high temperature. In addition, this technology is sometimes insufficient in maintaining airtightness when an inflator that generates higher temperature gas and a stronger stress is applied to the boundary between the inflation part and the non-inflation part due to the recent enlargement of the airbag is used.

[0004] In addition, the following patent document 2 discloses a technology that increases the friction between the warp and weft yarns when the fabric is made by having a specific amount of aromatic substances on the fiber surface, thereby suppressing the mesh of the expansion part and the non-expanded part not only at room temperature but also at high temperature. However, this technology is sometimes insufficient for the stress applied to the expansion part and the non-expanded part of the enlarged bag at high temperature, and the storage property is sometimes impaired due to the increase in friction between fibers.

[0005] As described above, there has been no disclosure of a base fabric for an airbag which has stable deployment properties, airtightness, and storage properties even when a large-sized airbag and a high-temperature inflator are used.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-183309

[0009] Patent Document 2: International Publication No. 2014 / 123090 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] In view of the above-mentioned technical level, the problem to be solved by the present invention is to provide a base fabric for materials, such as a base fabric for airbags, in which the mesh at the boundary between the expansion part and the non-expansion part is suppressed when making a bag body, the dynamic air permeability is low, and the base fabric can exhibit the characteristics of being not easy to break even at high temperatures.

[0012] Solutions for solving problems

[0013] The present inventors have conducted intensive studies and repeated experiments to solve the above-mentioned problems, and as a result, unexpectedly found that the problems can be solved by setting the following configuration, thereby completing the present invention.

[0014] That is, the present invention is as follows.

[0015] [1] A material fabric base fabric, characterized in that the material fabric base fabric is composed of fibers having a yarn strength of 6.6 cN / dtex to 8.5 cN / dtex obtained by disassembling the base fabric, the surface of the fabric is not subjected to resin coating, lamination or resin impregnation treatment, and the E1 of the warp and weft yarns of the material fabric base fabric are both 3 MPa to 25 MPa, and the E2 of the warp and weft yarns are both 10 MPa to 30 MPa.

[0016] E1 is the value obtained by dividing the increase in strength of the warp and weft yarns in the range of 0.4% to 4.4% elongation under 25°C and 150°C in the strength-elongation characteristic (FS) curve of the constituent fibers obtained by the edgecomb resistance test specified in ASTM D6479 by the total cross-sectional area of ​​the fibers in the measuring direction.

[0017] The E2 refers to: in the strength-elongation characteristic (FS) curve of the constituent fibers obtained by the edge combing resistance test specified in ASTM D6479, the value obtained by dividing the ratio of the increased strength of the warp yarn and the weft yarn under an environment of 25°C and an environment of 150°C and within the range of -4.8% to -0.8% of the elongation from the fiber breaking point by the total cross-sectional area of ​​the fibers in the measuring direction.

[0018] [2] The material woven fabric according to [1], wherein the dynamic air permeability of the fabric portion measured at an initial pressure of 100±5 kPa and between 30 kPa and 70 kPa in accordance with ASTM 6476 is 400 mm / s or less.

[0019] [3] The material woven fabric according to [1] or [2] above, wherein the amount of residual oil in the fabric is 200 ppm by weight or more and 800 ppm by weight or less.

[0020] [4] The material woven fabric according to any one of [1] to [3] above, wherein the woven fabric structure is a plain weave.

[0021] [5] The material woven fabric according to any one of [1] to [4], wherein the raw material of the fibers constituting the fabric is polyhexamethylene adipamide.

[0022] [6] An airbag produced using the material fabric base fabric described in any one of [1] to [5] above.

[0023] [7] The method for producing a base fabric for materials according to any one of [1] to [5], comprising the following steps:

[0024] Weaving process;

[0025] Unrefined or smelted at a temperature below 70°C;

[0026] Undried or dried at a temperature below 70°C;

[0027] A step of performing heat treatment at 150° C. or higher, wherein at the end of the heat treatment, a step of performing a shrinkage and stretching of 1% or more relative to the minimum width during the heat treatment is performed.

[0028] Effects of the Invention

[0029] The mesh of the boundary between the expansion part and the non-expansion part of the material fabric base cloth of the present invention is suppressed when the bag body is made, the dynamic air permeability is low, and the material fabric base cloth can also exhibit the characteristic of not being easy to break even at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a figure explaining the FS curve measured by ASTM_D6479 and the images of E1 and E2.

[0031] Figure 2 This is a schematic diagram for explaining the measurement of inter-fiber friction.

[0032] Figure 3 It is a schematic diagram of unfolding the test capsule.

[0033] Figure 4 This is a schematic diagram of the heat setting (heat treatment) process using a tenter frame. DETAILED DESCRIPTION

[0034] Hereinafter, embodiments of the present invention will be described in detail.

[0035] One embodiment of the present invention is a material fabric base fabric, characterized in that it is composed of fibers having a yarn strength of 6.6 cN / dtex to 8.5 cN / dtex obtained by disassembling the base fabric, and the surface of the fabric is not subjected to resin coating, lamination or resin impregnation treatment, and the E1 of the warp yarn and the weft yarn of the material fabric base fabric are both 3 MPa to 25 MPa, and the E2 is both 10 MPa to 30 MPa.

[0036] E1 is the value obtained by dividing the increase in strength of the warp and weft yarns in the elongation range of 0.4% to 4.4% under an environment of 25°C and an environment of 150°C by the total cross-sectional area of ​​the fibers in the measurement direction in the strength-elongation characteristic (FS) curve of the constituent fibers obtained by the edge combing resistance measurement specified in ASTM D6479,

[0037] The E2 refers to: in the strength-elongation characteristic (FS) curve of the constituent fibers obtained by the edge combing resistance test specified in ASTM D6479, the value obtained by dividing the increased strength of the warp yarn and the weft yarn in the range of -4.8% to -0.8% from the fiber breaking point under an environment of 25°C and an environment of 150°C by the total cross-sectional area of ​​the fibers in the measuring direction.

[0038] The material fabric base fabric of this embodiment can maintain airtightness from low temperature to high temperature when the bag is made by this structure, and the mesh at the boundary between the expansion part and the non-expansion part is suppressed, so it can also exhibit the characteristic of not being easy to break at high temperature.

[0039] In the fabric base cloth for materials of the present embodiment, the strength of the yarn (disassembled yarn) obtained by disassembling the base cloth is 6.6 cN / dtex to 8.5 cN / dtex. If the disassembled yarn strength is 6.6 cN / dtex or more, when the bag is made and unfolded, it can withstand the stress applied to the boundary portion of the expansion part and the non-expansion part, and can avoid rupture due to mechanical properties. It is more preferably 6.8 cN / dtex or more, and further preferably 7.0 cN / dtex or more. High yarn strength means that the orientation of the yarn is high, and the elongation of the fibers constituting the base cloth is small. Therefore, the air permeability of the base cloth can be suppressed to a low level, and then the mesh can be suppressed at the stitches. On the other hand, if the disassembled yarn strength exceeds 8.5 cN / dtex, sometimes a single yarn breaks and produces fuzz, and thus, the quality of the base cloth sometimes deteriorates. It is more preferably 8.0 cN / dtex or less, and further preferably 7.5 cN / dtex or less.

[0040] The total fineness of the fibers constituting the material woven fabric of the present embodiment is not particularly limited, but is preferably 135 dtex to 800 dtex, more preferably 215 dtex to 500 dtex, and even more preferably 230 dtex to 490 dtex from the viewpoint of the softness and storage properties of the fabric.

[0041] The single yarn fineness of the fibers constituting the material woven fabric of the present embodiment is not particularly limited, but is preferably 0.5 dtex to 10 dtex, more preferably 2 dtex to 7 dtex, and even more preferably 3 dtex to 6 dtex from the viewpoint of flexibility.

[0042] The E1 of the warp yarn and the weft yarn of the material fabric base fabric of this embodiment are both 3MPa to 25MPa, and E2 are both 10MPa to 30MPa. The E1 refers to: in the strength-elongation characteristic (FS) curve obtained when the edge combing resistance specified in ASTM D6479 is measured, the value obtained by dividing the strength increase of the warp yarn and the weft yarn in the range of 0.4% to 4.4% under an environment of 25°C and an environment of 150°C by the total cross-sectional area of ​​the fiber in the measuring direction. The E2 refers to: in the strength-elongation characteristic (FS) curve obtained when the edge combing resistance specified in ASTM D6479 is measured, the value obtained by dividing the strength increase of the warp yarn and the weft yarn in the range of -4.8% to -0.8% from the fiber breaking point under an environment of 25°C and an environment of 150°C by the total cross-sectional area of ​​the fiber in the measuring direction.

[0043] E1 is the resistance at which the woven yarn of the base fabric begins to deviate. If E1 is 3MPa or more, the woven yarn of the base fabric is not easy to deviate, and it is not easy to form mesh at the boundary between the expansion part and the non-expansion part when the bag is made, that is, the stitch. The reduction in airtightness caused by the mesh and the rupture caused by the penetration of hot gas can be suppressed. On the other hand, if E1 is below 25MPa, local mesh is not easy to form. Furthermore, the smaller the value of E1, the harder the base fabric becomes and the storage performance is not impaired. That is, E1 has an appropriate area for the stitch opening. E1 is more preferably 5MPa to 22MPa. E2 is the maximum resistance when the woven yarn of the base fabric deviates. If E2 is 10MPa or more, the air permeability of the base fabric itself can be suppressed when the stress applied to the base fabric under high pressure increases, and the airtightness of the base fabric under high pressure can be maintained. If E2 is below 30MPa, no local mesh will be produced. In particular, if E2 of both the warp and weft yarns at 150°C is high, the bag body in a high temperature and high pressure environment can reach a high ultimate pressure when absorbing impact and function without rupture. More preferably, E2 is 15 MPa to 25 MPa.

[0044] In this specification, the term "elongation in the strength-elongation characteristic (FS) curve of a base fabric obtained by measuring the edge combing resistance specified in ASTM D6479" means the ratio of the tensile elongation to the original length.

[0045] In this specification, the term "total fiber cross-sectional area in the measuring direction" of elongation refers to the area of ​​a perfect circular cross section calculated from the original yarn fineness.

[0046] Regarding the dynamic air permeability of the material fabric base fabric of the present embodiment, the dynamic air permeability of the base fabric portion measured between 30 kPa and 70 kPa is preferably 400 mm / s or less, and more preferably 350 mm / s or less when the initial pressure is set to 100 ± 5 kPa according to ASTM 6476. The smaller the dynamic air permeability is below 400 mm / s, the better the air tightness of the airbag body and the higher the deployment limit pressure. The lower limit of the dynamic air permeability is not particularly limited and can be 100 mm / s or more.

[0047] In the material fabric base fabric of the present embodiment, from the viewpoint of imparting softness to the base fabric, the amount of residual oil after finishing is preferably 200 wt ppm or more and 800 wt ppm or less, and more preferably 400 wt ppm or more and 600 wt ppm or less relative to the base fabric. Residual oil agent refers to a substance including spinning oil agent, warping oil agent, softening finishing agent, etc., and for example, composed of a smoothing agent, an emulsifier, and an antistatic agent. The less the amount of residual oil is 800 wt ppm or less, the more the mesh will be suppressed and the air permeability will be suppressed. On the other hand, by having more than 200 wt ppm, the softness of the base fabric is good, which is beneficial for bag forming.

[0048] Examples of the smoothing agent include dioctyl adipate, di(2-octyldodecyl) adipate, 1,6-hexanediol dioleate, dioleyl sebacate, dilauryl azelate, dioleyl adipate, dilauryl thiodipropionate, dioleyl thiodipropionate, bisphenol A dilaurate, ethylene glycol dioleate, polyethylene glycol dilaurate, 1,4-butanediol dioleate, glyceryl trilaurate, glyceryl trioleate, sorbitan trioleate, sorbitan tetraoleate, trimethylolpropane trilaurate, and pentaerythritol tetraoleate.

[0049] Examples of the emulsifier and antistatic agent include hydrogenated castor oil trioleate, AO adducts thereof, polyoxyethylene lauryl ether, polyoxyethylene oleyl ether, polyoxyethylene laurate, polyoxyethylene stearate, polyoxyethylene nonylphenol ether, ethylene oxide adducts of hydrogenated castor oil, ethylene oxide adduct trilaurate of hydrogenated castor oil, and ethylene oxide adduct trioleate of hydrogenated castor oil.

[0050] As the anionic surfactant of the emulsifier, inorganic salts such as sodium higher alcohol sulfate and potassium alkyl phosphate, and organic salts can be used.

[0051] The residual oil can be added by using a dedicated nozzle, a touch roll, or the like during spinning.

[0052] The residual oil agent may be added by immersion during warping, scouring, or water washing, and then adjusted to a predetermined residual amount by water washing or scouring.

[0053] Another embodiment of the present invention is a method for manufacturing the aforementioned material fabric base fabric, which comprises the following steps:

[0054] Weaving process;

[0055] Unrefined or smelted at a temperature below 70°C;

[0056] Undried or dried at a temperature below 70°C;

[0057] A step of performing heat treatment at 150° C. or higher, wherein at the end of the heat treatment, a step of performing a shrinkage and stretching of 1% or more relative to the minimum width during the heat treatment is performed.

[0058] In the production of the material woven fabric base fabric of the present embodiment, the processing steps after weaving are important for obtaining preferred base fabric properties.

[0059] In weaving, if it is a water jet loom, the residual oil component on the base fabric through the water flow sometimes becomes the preferred amount of oil, and it is also preferred to enter the subsequent process without refining. In addition, when refining is performed to make the amount of residual oil component on the base fabric an appropriate value, if it is over-refined, E1 and E2 sometimes increase excessively, so it is necessary to pay attention. At this time, the refining temperature is preferably below 70°C and above room temperature, and more preferably below 60°C and above room temperature. If it is not refined or refined to below 70°C, heat setting can be performed that does not fully show the shrinkage force of the woven yarn but fully shows the structural tightening of the base fabric in the final process of processing. As a result, E1 is only too high in appearance, but the situation of stitch opening disappears. Refining can be water washing, or a refining agent can be further used. When using a refining agent, sodium hydroxide, sodium carbonate, etc. can be used. In addition, chelating agents and surfactants are sometimes used. Applying tension in the warp direction in the scouring step is useful because it stabilizes the transport of the fabric. However, when the temperature is raised, even if tension is applied to the fabric in a wet state, it does not suppress the contraction force of the woven yarn.

[0060] Next, the scouring cloth is preferably directly heat-set. Here, when the scouring cloth is dried and provided to the subsequent process, the drying temperature is preferably 70°C or less and above room temperature. If it is not dried or dried to 70°C or less, heat setting can be performed so that the shrinkage of the woven yarn is not fully manifested but the structure of the base fabric is fully tightened in the final process of processing. As a result, E1 is only too high in appearance, but the situation of stitch opening is eliminated.

[0061] After scouring or drying, in the heat setting (heat treatment) step, the heat setting temperature is preferably 150°C to 190°C. If the heat setting temperature is 150°C or higher, the setting is sufficient, and a base fabric with high E1 and E2 is formed, with few meshes and low air permeability even under high pressure. The situation observed in the case of insufficient setting, such as high E2 in the tensioned state of the fabric and low air permeability under high pressure, but excessively high E1 and open stitches, disappears.

[0062] In the heat setting process, a tenter is used, and from the viewpoint of preventing excessive decrease in E1 and E2, it is preferred not to use a drying drum during drying. This is because when a wet base fabric is dried using a drying drum, due to shrinkage in the width direction (weft direction), E1 and E2 may decrease, and the width fixation during the drying process may become unstable, resulting in uneven physical properties.

[0063] When heat setting is performed using a tenter, the overfeed in the warp direction is preferably 0 to 5%, more preferably 0 to 2%. The overfeed is adjusted so that E1 at 25°C and 150°C is close to the center of the range of 3 MPa to 25 MPa, and E2 is close to the center of the range of 10 MPa to 30 MPa.

[0064] When heat setting is performed using a tenter, the maximum shrinkage due to heat setting represented by the following formula is preferably 0 to 8%.

[0065] Maximum shrinkage during heat setting (%) = [(heat setting inlet width - heat setting minimum width) / heat setting inlet width] × 100

[0066] {Wherein, “heat setting inlet width” is Figure 4 The symbol (1) indicates the width of the blank at the entrance of the heat setting heating furnace (heat setting entrance width), and the "minimum width of heat setting" is Figure 4 The symbol (2) indicates the minimum width of the blank in the heat setting heating furnace (the minimum width for heat setting).}

[0067] In order to utilize the heat shrinkage force of the constituent fibers to tighten the fabric structure, the shrinkage is not allowed to shrink freely, but the shrinkage rate is limited to control it. Preferably, the maximum shrinkage after heat setting is 8% or less, and the smaller it is, the easier it is to improve E1 and E2. The maximum shrinkage after heat setting is more preferably 6% or less, and further preferably 4% or less.

[0068] Furthermore, the heat setting process is preferably carried out in multiple stages. In particular, the tightening of the base fabric structure in the final stage of the heat setting process is important.

[0069] The final shrinkage during heat setting represented by the following formula is preferably 0 to 6%.

[0070] Final shrinkage after heat setting (%) = [(heat setting inlet width - heat setting outlet width) / heat setting inlet width] × 100

[0071] {Wherein, “heat setting outlet width” is Figure 4 The width of the blank at the outlet of the heat setting heating furnace (heat setting outlet width) represented by the symbol (3) is the width of the blank at the outlet of the heat setting heating furnace (heat setting outlet width), and the "heat setting inlet width" is the width of the blank at the outlet of the heat setting heating furnace (heat setting outlet width). Figure 4The symbol (1) represents the billet width at the entrance of the heat setting heating furnace (heat setting entrance width).}.

[0072] Furthermore, the shrinkage defined by {maximum shrinkage during heat setting (%) - final shrinkage during heat setting (%)} is preferably 1 to 4%. By making the final width of heat setting (heat setting outlet width (3)) larger than the minimum width of heat setting (minimum width of heat setting (2)), the structural relaxation of the base fabric can be suppressed. This is called shrinkage stretching. By making the shrinkage amount greater than 1%, E1 and E2 can be increased at the same time, and a low mesh and low air permeability base fabric can be obtained. The shrinkage amount is more preferably greater than 2%. The shrinkage effect of the base fabric achieved by making the final shrinkage during heat setting (heat setting outlet width (3)) larger than the minimum shrinkage during heat setting (minimum width of heat setting (2)) is effective on the basis that the heat setting process in the previous stage is at a sufficient temperature and the fabric structure is fully tensioned by showing a shrinkage force. If the shrinkage amount is less than 4%, the fabric finishing is uniform.

[0073] The woven structure of the material fabric base fabric of the present embodiment is preferably a plain weave structure, which is advantageous for the strength of the base fabric. However, other woven structures or combined designs may be used.

[0074] As the raw materials (materials) of the constituent fibers of the resource fabric base cloth of the present embodiment, polyethylene terephthalate, polyamide 6, 610, 46, 66, polyethylene naphthalate, etc. can be listed. From the viewpoint of heat resistance, strength and cost, polyamide 66 and polyethylene terephthalate are preferred, and polyamide 66 (polyhexamethylene adipamide) is particularly preferred.

[0075] Example

[0076] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0077] First, the measurement and evaluation methods used in Examples and the like are described.

[0078] (1) Fineness (dtex), strength (N), and tenacity (cN / dtex) of raw yarn and disassembled yarn (multifilament)

[0079] The fineness, strength and tenacity of the fibers were measured in accordance with JIS_L1013.

[0080] (2) Oil dosage of raw yarn

[0081] The amount (wt%) of the spinning oil or the like contained in the raw yarn was measured in accordance with JIS_L1013 (8.27). Cyclohexane was used as the extraction solvent.

[0082] (3) Residual oil dosage of base fabric

[0083] The residual oil amount (the amount of oil agent adhered) was determined by cutting out the base fabric, subjecting it to Soxhlet extraction with cyclohexane, then evaporating the solvent of the extract, and dividing the residual oil by the weight of the charged base fabric.

[0084] (4) Friction between yarns of the original yarn

[0085] Regarding the friction between the original yarns, Figure 2 As shown, the original yarn is twisted three times to make them contact each other, the load on the yarn supply side (weight T1) is set to 140g, the pulling tension after twisting is measured (load sensor T2), and T2 / T1 is set as the friction force f between yarns.

[0086] (5) Strength (N) and elongation (%) of base fabric

[0087] The strength and elongation of the base fabric were measured by the strip method of JIS_L1096.

[0088] (6) Weaving density of warp and weft yarns

[0089] The weaving density of the warp and weft was measured at five points each of the warp and weft using FX3255 manufactured by TEXTEST, and the average value was taken as the average value.

[0090] (7)E1

[0091] E1 is set to the following value: the value obtained by dividing the strength increase in the range of 0.4% to 4.4% elongation measured by the method of ASTM_D6479 at 25°C (room temperature) and 150°C by the calculated value of the total cross-sectional area of ​​the fiber in the measurement direction shown in the following formula 1. The sample width is set to 5 cm. The sample is installed at intervals of 20 cm using a scraping comb tool and a clamping tool, which is taken as the original length of the sample, and the ratio of the tensile elongation is set as the elongation.

[0092] A=(d*D*(5 / 2.54)) / (ρ*10^10)…Equation 1

[0093] {where A is the total cross-sectional area of ​​the fiber (m^2), d is the fiber fineness (dtex), D is the weaving density in the clamping width direction of the sample, and is the number of yarns per 2.54 cm, and ρ is the density of nylon 66, 1.14 (g / cm^3).}

[0094] (8)E2

[0095] E2 is calculated as follows: The strength increased from the breaking point (the point where the load drop is measured) in the environment of 25°C (room temperature) and 150°C by the method of ASTM_D6479 in E1 above, and in the range of -4.8% to -0.8%, is calculated using the same calculation formula as E1. The sample width is 5 cm.

[0096] (9) Mesh

[0097] like Figure 3 As shown in the figure, a base cloth is sewn with a chain stitch of 65 stitches / dm using a sewing thread formed by a twisted yarn of 1350 dtex to produce a bag with a gas inlet of 8 cm width × 10 cm length and a diameter of 30 cm. The bag is turned inside out to obtain an airbag, and the obtained airbag is placed in a hot air dryer at 150°C and left for 10 minutes. Then, while the airbag is placed in the dryer, helium is instantly supplied to expand the bag under the conditions of a pressure of 5 MPa, a nozzle of 0.6 inches, and a tank capacity of 250 cc using a CGS system manufactured by MICRO SYSTEM. The bag is then taken out and, after being sufficiently cooled, the maximum mesh size of the sewn portion of the bag is measured with a vernier caliper.

[0098] (10) Dynamic air permeability of base fabric

[0099] The dynamic air permeability of the base fabric was measured in accordance with ASTM_D6476 with an initial pressure of 100±5 kPa, and was measured as an average value of the dynamic air permeability between 30 and 70 kPa.

[0100] (11) High temperature near-expansion evaluation (high temperature crack resistance)

[0101] A driver's airbag with a volume of 60L is sewn without vents, and an inflator that is a pyrotechnic inflator with a tank pressure of 200kPa is installed. Heat the entire thing in an 80°C oven and immediately place it on an evaluation table. Ignite it while the temperature is not lowered. Expand it toward a proximity plate at a distance of 15cm. Samples that are not broken and have no changes in the sewing part are evaluated as "○". Samples that are not broken but have disorder such as the base fabric spreading out in the sewing part are evaluated as "△". Samples that have broken bags are rated as "×".

[0102] [Example 1]

[0103] A polyamide 66 resin having a relative viscosity of 80 and 90% formic acid was melt-spun at 300°C, and a spinning oil of 0.8% by weight was applied to the fiber by a touch roll while cooling. The fiber was then stretched to 4.9 times by a stretching roll at 200°C, and interlaced by compressed air to obtain a raw yarn having a fineness of 470 dtex and a filament number of 136. The strength of the raw yarn was 40.5 N. The raw yarn was used without sizing, and LWT710 manufactured by Toyota Automatic Loom Co., Ltd. was used. Under the conditions of a reed width of 220 cm and a weaving warp tension of 0.24 cN / dtex, two 22dtex nylon 6 single yarns were used for interlacing yarns at both selvedges, and 10 nylon 66 yarns were used for reinforcing yarns at both ends in the same manner as the base yarn, to obtain a plain weave blank having a warp density of 47 yarns / inch. After that, the fabric was washed with water at 30-30-30°C for 40 seconds in a three-stage bath, and then, without using a drying drum, the fabric was continuously treated with a pin-card tentering machine at 80°C at the inlet, 190°C during heat setting, and 130°C at the end for 50 seconds in total, with an overfeed of 0%, a maximum shrinkage of 6% during heat setting, a final shrinkage of 4% during heat setting, and a shrinkage of 2%. A base fabric with a target warp and weft of 49 strands / inch was obtained. The obtained unraveled yarn strength and various physical properties of the base fabric are shown in Tables 1 and 2 below.

[0104] [Example 2]

[0105] The same fibers as in Example 1 were used, the warp and weft density during weaving was set to 51 yarns / inch, and the same weaving conditions were used, and the shaping was performed under the same conditions as in Example 1 to obtain a base fabric with a target warp and weft of 53 yarns / inch. The obtained unraveled yarn strength and various physical properties of the base fabric are shown in the following Tables 1 and 2.

[0106] [Example 3]

[0107] The same fibers as in Example 1 were used, the warp density was set to 53 yarns / inch, and the same weaving conditions were used, and the shaping was performed under the same conditions as in Example 1 to obtain a base fabric with a target warp and weft of 55 yarns / inch. The obtained unraveled yarn strength and various physical properties of the base fabric are shown in the following Tables 1 and 2.

[0108] [Example 4]

[0109] A polyamide 66 resin having a relative viscosity of 80 and 90% formic acid was melt-spun at 300°C, and a spinning oil of 0.8% by weight was applied to the fiber by a touch roll while cooling. The fiber was then stretched to 4.8 times by a stretching roll at 200°C, and interlaced by compressed air to obtain a raw yarn having a fineness of 350 dtex and a filament number of 136. The strength of the raw yarn was 30.0 N. The raw yarn was used without sizing, and LWT710 manufactured by Toyota Automatic Loom Co., Ltd. was used. Under the conditions of a reed width of 220 cm and a weaving warp tension of 0.24 cN / dtex, two 22 dtex nylon 6 single yarns were used for interlacing yarns at both selvedges, and 10 nylon 66 yarns were used for reinforcing yarns at both ends in the same manner as the base yarn, to obtain a plain weave blank having a warp density of 58 yarns / inch. The same processing as in Example 1 was then performed to obtain a base fabric having a target warp and weft of 60 yarns / inch. The obtained unraveled yarn strength and various physical properties of the base fabric are shown in Tables 1 and 2 below.

[0110] [Example 5]

[0111] A polyamide 66 resin having a relative viscosity of 80 in 90% formic acid was melt-spun at 300°C, and a spinning oil of 0.8% by weight was applied to the fibers by a touch roll while cooling. The fibers were then stretched to 4.7 times by a stretching roll at 200°C, and interlaced by compressed air to obtain a raw yarn having a fineness of 235 dtex and a filament number of 72. The strength of the raw yarn was 20.0 N. The raw yarn was used without sizing, and a Toyota Automatic Loom Co., Ltd. LWT710 was used. Under the conditions of a reed width of 220 cm and a weaving warp tension of 0.24 cN / dtex, two 22 dtex nylon 6 single yarns were used for interlacing yarns at both selvedges, and 10 nylon 66 yarns were used for reinforcing yarns and base yarns at both ends, respectively, to obtain a plain weave blank having a warp density of 69 yarns / inch. The same processing as in Example 1 was performed to obtain a target base fabric of 74 yarns / inch. The obtained unraveled yarn strength and various physical properties of the base fabric are shown in Tables 1 and 2 below.

[0112] [Table 1]

[0113]

[0114] [Table 2]

[0115]

[0116] [Comparative Example 1]

[0117] The same fibers as in Example 1 were used for the same weaving. Thereafter, the fabric was washed with water at 30-30-30°C for a total of 40 seconds using a three-stage bath, and then drum dried at 110°C for 60 seconds, and temporarily rolled up after drying. Next, it was immersed in a silicone resin emulsion bath with a solid content of 1500ppm, and then, a setting treatment was performed using a needle comb tentering machine with an inlet of 80°C, a heat setting temperature of 190°C, a final setting of 130°C for a total of 50 seconds, an overfeed of 4%, a maximum heat setting shrinkage of 2%, a final heat setting shrinkage of 2%, and a shrinkage of 0%, to obtain the target base fabric. The obtained disassembled yarn strength and various physical properties of the base fabric are shown in the following Tables 3 and 4. E1 and E2 are both low, with more high-pressure air permeability and a large stitch opening. The high temperature approaching expansion evaluation is △.

[0118] [Comparative Example 2]

[0119] A polyamide 66 resin having a relative viscosity of 80 in 90% formic acid was melt-spun at 300°C, and 0.8 wt% of an oil obtained by adding 30 wt% of bisphenol A dilaurate to the spinning oil of Example 1 was applied to the fiber by a touch roll while cooling. The fiber was then stretched to 4.9 times by a stretching roll at 200°C, and interlaced by compressed air to obtain a raw yarn having a fineness of 470 dtex and a filament number of 136. The strength of the raw yarn was 40.5 N. The raw yarn was used without sizing, and LWT710 manufactured by Toyota Automatic Loom Co., Ltd. was used. Under the conditions of a reed width of 220 cm and a weaving warp tension of 0.24 cN / dtex, two 22 dtex nylon 6 single yarns were used for interlacing yarns at both selvedges, and 10 nylon 66 yarns were used for reinforcing yarns at both ends in the same manner as the base yarn, to obtain a plain weave blank having a warp density of 51 yarns / inch. After that, it was washed with water at 80-80-80°C for a total of 40 seconds using a three-stage bath, and then dried on a drying drum at 110°C for 40 seconds without temporary winding. It was subjected to a setting treatment using a needle-combing tenter at 100°C for a total of 50 seconds, with an overfeed of 4%, a maximum shrinkage of 2% for heat setting, a final shrinkage of 2% for heat setting, and a shrinkage of 0%, to obtain the target base fabric of 53 strands / inch. The strength of the obtained disassembled yarn and various physical properties of the base fabric are shown in the following Tables 3 and 4. E2 is too high, high pressure permeability is high, and the stitch opening is large. High temperature close to the development is evaluated as △.

[0120] [Comparative Example 3]

[0121] A polyamide 66 resin with a relative viscosity of 80 and 90% formic acid was melt-spun at 300°C, and 0.8% by weight of a spinning oil was applied to the fiber by a contact roller while cooling. The fiber was then stretched to 4.0 times by a stretching roller at 200°C, and interwoven with compressed air to obtain a raw yarn with a fineness of 470 dtex and 136 filaments. The strength of the raw yarn was 35.0N. The raw yarn was processed in the same manner as in Example 1 to obtain the target base fabric. The strength of the resulting disassembled yarn and various physical properties of the base fabric are shown in Tables 3 and 4 below. E1 and E2 are both low, with more high-pressure air permeability and a slightly larger stitch opening. The high temperature approaching expansion evaluation was ×.

[0122] [Comparative Example 4]

[0123] A polyamide 66 resin having a relative viscosity of 80 and 90% formic acid was melt-spun at 300°C, and a spinning oil of 1.5% by weight was applied to the fiber by a touch roll while cooling. The fiber was then stretched to 4.9 times by a stretching roll at 200°C, and interlaced by compressed air to obtain a raw yarn having a fineness of 470 dtex and a filament number of 136. The strength of the raw yarn was 40.5 N. The raw yarn was used without sizing, and LWT710 manufactured by Toyota Automatic Loom Co., Ltd. was used. Under the conditions of a reed width of 220 cm and a weaving warp tension of 0.24 cN / dtex, two 22dtex nylon 6 single yarns were used for interlacing yarns at both selvedges, and 10 nylon 66 yarns were used for reinforcing yarns at both ends in the same manner as the base yarn, to obtain a plain weave blank having a warp density of 51 yarns / inch. Afterwards, without washing in a bath, a setting treatment was performed using a needle-combing tentering machine with an inlet of 80°C, a heat setting of 190°C, a final setting of 130°C for a total of 50 seconds, an overfeed of 0%, a maximum shrinkage of 6% during heat setting, a final shrinkage of 4% during heat setting, and a shrinkage of 2%, to obtain the target 53 strands / inch base fabric. The strength of the obtained disassembled yarn and various physical properties of the base fabric are shown in the following Tables 3 and 4. E1 and E2 are both low, with more high-pressure air permeability and a large stitch opening. The high temperature close to the development evaluation is △.

[0124] [Comparative Example 5]

[0125] A polyamide 66 resin having a relative viscosity of 80 and 90% formic acid was melt-spun at 300°C, and a spinning oil of 0.5% by weight was applied to the fiber by a touch roll while cooling. The fiber was then stretched to 4.9 times by a stretching roll at 200°C, and interlaced by compressed air to obtain a raw yarn having a fineness of 470 dtex and a filament number of 136. The strength of the raw yarn was 40.5 N. The raw yarn was used without sizing, and LWT710 manufactured by Toyota Automatic Loom Co., Ltd. was used. Under the conditions of a reed width of 220 cm and a weaving warp tension of 0.24 cN / dtex, two 22dtex nylon 6 single yarns were used for interlacing yarns at both selvedges, and 10 nylon 66 yarns were used for reinforcing yarns at both ends in the same manner as the base yarn, to obtain a plain weave blank having a warp density of 49 yarns / inch. After that, after immersing in the first bath containing a nonionic surfactant at 30°C for 10 seconds, washing in water at 90-90°C for a total of 30 seconds in the second and third stages, without using a drying drum, the yarn was set continuously using a needle-combing tentering machine at 80°C at the inlet, 190°C during setting, 130°C at the end, and a total of 50 seconds of setting, overfeed of 0%, maximum shrinkage of heat setting of 6%, final shrinkage of heat setting of 4%, and shrinkage of 2%, to obtain the target 53 strands / inch base fabric. The obtained disassembled yarn strength and various physical properties of the base fabric are shown in the following Tables 3 and 4. E2 is too high, high pressure permeability is high, and the stitch opening is large. High temperature close to the development is evaluated as ×.

[0126] [Comparative Example 6]

[0127] The same raw yarn as in Example 1 was used, and the same weaving was performed. After the blank was temporarily made, it was washed with water at 30-30-30°C for a total of 40 seconds using a three-stage bath. Without using a drying drum, it was continuously shaped at 80°C at the entrance of the needle-combing tentering machine, 190°C during shaping, and 130°C for a total of 50 seconds, with overfeed of 0%, maximum shrinkage of heat setting of 6%, final shrinkage of heat setting of 6%, and shrinkage of 0%, to obtain the target base fabric. The strength of the obtained disassembled yarn and various physical properties of the base fabric are shown in the following Tables 3 and 4. E1 and E2 are both low, with more high-pressure air permeability and a large stitch opening. The high temperature close to the expansion evaluation is △.

[0128] [Comparative Example 7]

[0129] The same weaving as in Example 2 was carried out. After the blank was temporarily prepared, it was washed with water at 60-90-90°C for a total of 40 seconds using a three-stage bath. Without using a drying drum, it was continuously shaped at 80°C at the entrance of the needle-combing tentering machine, 190°C during shaping, and 130°C for a total of 50 seconds, with overfeed of 0%, maximum shrinkage of heat setting of 6%, final shrinkage of heat setting of 4%, and shrinkage of 2%, to obtain the target 53 strands / inch base fabric. The strength of the obtained disassembled yarn and various physical properties of the base fabric are shown in the following Tables 3 and 4. E1 is too high, high pressure permeability is high, and the stitch opening is large. High temperature close to the expansion evaluation is ×.

[0130] [Comparative Example 8]

[0131] The same weaving as in Example 2 was carried out. After the blank was temporarily prepared, it was washed with water at 30-30-30°C for a total of 40 seconds using a three-stage bath, and then drum dried at 110°C for 60 seconds. After drying, it was temporarily wound up. Next, the setting was carried out at 80°C at the entrance of the needle-combing tentering machine, 190°C during setting, 130°C at the end, and a total of 50 seconds of setting, overfeed of 0%, maximum shrinkage of heat setting of 6%, final shrinkage of heat setting of 4%, and shrinkage of 2%, to obtain the target 53 strands / inch base fabric. The strength of the obtained disassembled yarn and various physical properties of the base fabric are shown in the following Tables 3 and 4. E1 is too high, high pressure permeability is high, and the stitch opening is large. High temperature close to the expansion is evaluated as ×.

[0132] [Comparative Example 9]

[0133] The same weaving as in Example 2 was carried out. After the blank was temporarily prepared, it was washed with water at 30-30-30°C for a total of 40 seconds using a three-stage bath. Without using a drying drum, it was continuously shaped at 80°C at the entrance of the needle-combing tentering machine, 130°C during shaping, 130°C at the end, and a total of 50 seconds of shaping, overfeeding of 0%, maximum shrinkage of heat setting of 6%, final shrinkage of heat setting of 4%, and shrinkage of 2%, to obtain the target 53 strands / inch base fabric. The strength of the obtained disassembled yarn and various physical properties of the base fabric are shown in the following Tables 3 and 4. E1 is too high, high pressure permeability is high, and the stitch opening is large. High temperature close to the expansion evaluation is ×.

[0134] [Table 3]

[0135]

[0136] [Table 4]

[0137]

[0138] The E1 and E2 of the base fabrics of Examples 1 to 5 are within the specified range, the boundary between the expansion part and the non-expansion part when the bag is made, that is, the mesh of the sewn part is suppressed, the dynamic air permeability of the base fabric is as low as 400 mm / s or less, and the characteristic of not being easy to break can be exerted even at high temperatures. In contrast, in the base fabrics of Comparative Examples 1 to 9, E1 and E2 are not within the specified range, the boundary between the expansion part and the non-expansion part when the bag is made, that is, the mesh of the sewn part is large, the dynamic air permeability of the base fabric does not decrease, and the characteristic of not being easy to break cannot be exerted at high temperatures.

[0139] Industrial Applicability

[0140] The material fabric base cloth involved in the present invention can suppress the mesh of the boundary part between the expansion part and the non-expansion part, that is, the sewn part, when making the bag body, has low dynamic air permeability, and can also exhibit the characteristic of not being easy to break even at high temperature. Therefore, it can be suitable for use as a material base cloth, especially a base cloth for airbags.

[0141] Description of Reference Numerals

[0142] 1 yarn

[0143] 2 Heavy Objects (T1)

[0144] 3 Force sensor (T2)

[0145] 4 pulleys

[0146] (1) Heat setting inlet width

[0147] (2) Minimum width for heat setting

[0148] (3) Heat setting outlet width

Claims

1. A fabric base fabric for materials, characterized in that: The material fabric base cloth is composed of raw yarn, and the strength of the yarn obtained by disassembling the base cloth is 6.6 cN / dtex to 8.5 cN / dtex, and the surface of the cloth is not subjected to resin coating, lamination or resin impregnation treatment. The E1 of the warp and weft yarns of the material fabric base cloth are both 3MPa~25MPa, and the E2 are both 10MPa~30MPa. E1 is the value obtained by dividing the increase in strength of the warp and weft yarns in the elongation range of 0.4% to 4.4% at 25°C and 150°C by the total cross-sectional area of ​​the fibers in the measurement direction in the strength-elongation characteristic (FS) curve of the constituent fibers obtained by the edge combing resistance measurement specified in ASTM D6479. The E2 is a value obtained by dividing the ratio of the increased strength of the warp yarn and the weft yarn in the range of -4.8% to -0.8% of the elongation from the fiber breaking point under an environment of 25°C and an environment of 150°C by the total cross-sectional area of ​​the fiber in the measuring direction in the strength-elongation characteristic (FS) curve of the constituent fibers obtained by the edge combing resistance measurement specified in ASTM D6479.

2. The material fabric base fabric according to claim 1, wherein: The strength of the yarn is 6.8 cN / dtex to 8.0 cN / dtex.

3. The material fabric base fabric according to claim 1, wherein: The strength of the yarn is 7.0 cN / dtex to 7.5 cN / dtex.

4. The material fabric base fabric according to claim 1, wherein: The fineness of the raw yarn constituting the base fabric is 135dtex~800dtex.

5. The material fabric base fabric according to claim 1, wherein: The single yarn fineness of the original yarn constituting the base fabric is 0.5dtex~10dtex.

6. The material fabric base fabric according to claim 1, wherein: The E1 is 5MPa~22MPa.

7. The material fabric base fabric according to claim 1, wherein: The E2 is 15MPa~25MPa.

8. The material fabric base fabric according to claim 1, wherein: According to ASTM 6476, the initial pressure is set to 100±5kPa, and the dynamic air permeability of the base fabric measured between 30kPa and 70kPa is less than 400mm / s.

9. The material fabric base fabric according to claim 8, wherein: The dynamic air permeability is greater than or equal to 100 mm / s and less than or equal to 350 mm / s.

10. The material fabric base fabric according to any one of claims 1 to 9, wherein The amount of residual oil is 200 ppm by weight or more and 800 ppm by weight or less based on the base fabric.

11. The material fabric base fabric according to claim 10, wherein: The residual oil amount is 400 ppm by weight or more and 600 ppm by weight or less with respect to the base fabric.

12. The material fabric base fabric according to any one of claims 1 to 9 and 11, wherein the fabric structure is a plain weave.

13. The material fabric base fabric according to any one of claims 1 to 9 and 11, wherein The raw material of the raw yarn constituting the base fabric is polyhexamethylene adipamide.

14. An airbag manufactured using the material fabric base fabric according to any one of claims 1 to 13.

15. The method for producing a base fabric for materials according to any one of claims 1 to 13, comprising the following steps: Weaving process; Unrefined or smelted at a temperature below 70°C; Undried or dried at a temperature below 70°C; A step of performing heat treatment at 150° C. or higher, wherein at the end of the heat treatment, a shrinkage stretching of 1% or more relative to the minimum width during the heat treatment is performed.

16. The method for producing a base fabric for materials according to claim 15, wherein: In the step of performing the heat treatment, the heat treatment temperature is 150°C to 190°C.

17. The method for producing a base fabric for materials according to claim 15, wherein: In the step of performing the heat treatment, a shrinkage stretching is performed at a stage where the heat treatment is completed by 2% or more and 4% or less of the minimum width during the heat treatment.

Citation Information

Patent Citations

  • Woven base cloth for air-bag

    JP2015183309A

  • Fabric for airbag and fabric roll

    WO2014123090A1

  • Base fabric for non-coated air bag

    JP2009235593A